液压挖掘机工作装置综合优化研究 - 姜饶保; 黄斌; 何清华; 贺继林 (Jixie chuandong)
The backhoe working device of hydraulic excavator is a typical openedchain four-bar mechanism,the distribution of it’s joints is very important to the working performance and useful life.It’s hard to get the satisfactory optimal result by routine methods.So,an integrative optimization model of working device is built to be optimized using genetic algorithm.The experimental results show that the integrative optimization method based on genetic algorithm is faster and more effective than traditional optimization method;the integrative working performance of the improved working device is improved largely.